Current Issues in Public Utilities and Public Policy Empirical Studies Focusing on Japan - Mizutani, Fumitoshi; Urakami, Takuya; Nakamura, Eri. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book is novel in that it reveals significant issues of economics, management and business fields currently observed in network industries such as public utilities and transportation, and provides empirical evidence of their mechanisms and policy implications from various perspectives. This is a holistic collection of literature on public utilities economics and management, since the industries discussed include a wide range such as electricity, water supply, sewerage, transport, and postal service, which compound social infrastructure as public benefit service, and the issues examined contain not only economics topics such as cost, efficiency, and productivity, but also management topics such as governance, strategy and organizational restructuring. The book also investigates general private companies to derive future implications for policy and governance of public utilities, and covers multiple countries such as Japan, the US, and Vietnam. It demonstrates various empirical approaches and methodologies for public utility analysis through 17 chapters by experts in each field, which contributes to further cultivation of empirical studies in public utilities.
Introduction -- An Analysis of the Effect of Demand Response on Electricity Consumption: Assessing Households' Heterogeneous Reaction to Dynamic Pricing -- Estimation of Tap Water Demand in Japan: A Panel Data Analysis -- Economies of Scale and Consolidation Effects in the Japanese Sewerage Industry -- Productivity Measurement and Decomposition of Total Factor Productivity in Japan's Postal and Parcel Delivery Industry -- Preferential Slot Allocation for LCCs at a Congested Airport, and Airfare: The Case of Haneda Airport in Tokyo -- The Impact of Airport Concession on Technical Efficiency: Evidence from Major Airports in Japan.
Keywords: Urban economics; Industrial policy; Public administration; Transportation; Economic policy; Microeconomics; Urban Economics; Regulation and Industrial Policy; Public Sector Studies; Transportation Economics; Economic Policy; Market Structure and Economic Design